Requirements for Building Thermal Conditions under Emergency Operations in Cold Climates - Zhivov Alexander M.; Rose William B.; Patenaude Raymond E.; Williams W. Jon (E3S Web of Conferences, 2021)
This paper provides recommendations on thermal and moisture parameters in different types of buildings under emergency operation in cold/arctic climates. We consider three scenarios under normal operating conditions: occupied, temporarily unoccupied, and long-term unoccupied. These thermal parameters are necessary to: (1) perform required work safely and efficiently, (2) support building processes, and (3) support long-term integrity of the building under emergency conditions (i.e., interruption of fuel, steam, hot water, and electrical service that interrupts building space conditioning). Under emergency conditions, requirements of thermal parameters for different categories of buildings may change. Mission critical areas can be conditioned to levels that support the agility of personnel who perform critical operations, but not to optimal comfort levels. Critical process requirements are given priority. This paper was developed for military applications, based on research performed under the International Energy Agency’s Energy in Buildings and Communities Program, Annex 73; under the Department of Defense Environmental Security Technology Certification Program project EW18-D1-5281, “Technologies Integration to Achieve Resilient, Low-Energy Military Installations,” and under the Office of the Deputy Assistant Secretary of the Army project “Thermal Energy Systems Resiliency for Army Installations located in cold climates.” Results are applicable to similar public and private sector buildings.